Integrated nematode management of root lesion and root-knot nematodes in soybean in Brazil - Soares, Pedro Luiz Martins [UNESP]; Nascimento, Daniel Dalvan [UNESP] (CABI Publishing, 2021)
This chapter focuses on the economic importance, host range, geographical distribution, damage symptoms and biology and life cycle of root lesion and root-knot nematodes infesting soyabean in Brazil, i.e. Pratylenchus brachyurus, Meloidogyne javanica and M. incognita. Some information on their interactions with other nematodes and pathogens, efficacy and optimization of some recommended integrated nematode management strategies and future outlook and research requirements for nematode management are also presented.